2021
DOI: 10.1101/2021.12.16.472979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemoproteomics of microbiota metabolites reveals small-molecule agonists for orphan receptor GPRC5A

Abstract: The microbiota generates diverse metabolites that can engage multiple pathways to modulate host physiology and disease, but their protein targets and mechanism(s) of action have not been fully elucidated. To address this challenge, we focused on indole-3-acetic acid (IAA), a prominent microbiota metabolite, and developed IAA-based chemical reporters for proteomic studies. We discovered that IAA interacts with many proteins in host cells, including small-molecule transporters, receptors and metabolic enzymes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Nonetheless, the identification of novel metabolite protein interactions may guide the exploration of structurally related metabolites that may yield more active agonists or antagonists of newly identified protein targets. 108 Given the increasingly frequent discoveries of microbiota and their metabolites in host physiology and disease, we hope this Perspective on chemoproteomics inspires the development and application of new chemical reporters to elucidate the mechanisms and functions of microbiota metabolites in health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, the identification of novel metabolite protein interactions may guide the exploration of structurally related metabolites that may yield more active agonists or antagonists of newly identified protein targets. 108 Given the increasingly frequent discoveries of microbiota and their metabolites in host physiology and disease, we hope this Perspective on chemoproteomics inspires the development and application of new chemical reporters to elucidate the mechanisms and functions of microbiota metabolites in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…To explore additional indole metabolite protein targets, our laboratory developed metabolic and photoaffinity reporters derived from indole acetic acid (IAA) (Figure 5A,B) and employed chemoproteomic profiling of IAA-interacting proteins in intestinal epithelial cells. 108 Interestingly, we identified many unpredicted IAA-interacting proteins, including small molecule transporters, metabolic enzymes, innate immune-associated effectors, and orphan GPCRs. Notably, our functional studies showed that IAA can interact with GPRC5A, an orphan GPCR tumor suppressor, but did not affect its activity.…”
Section: Chemical Reportersmentioning
confidence: 98%
See 3 more Smart Citations